Denunciation, blame and the moral turn in public life. (April 2019) - Márquez-Reiter, Rosina; Haugh, Michael
Highlights: Public denunciations involve ritual destruction of the moral standing of the target. The moral turn involves a broadening of what counts as a public figure. Constraints on publicly denouncing immoral behavior are on the wane. Abstract: Public denunciations involve ritual destruction of the moral standing of the target. They are intimately related to the assigning of blame and to the alleged perpetrator's concomitant denial of wrongdoing. While public denunciations are not a new phenomenon, what has arguably changed in recent years is the loosening of strictures on publicly denouncing immoral behavior, even when (alleged) moral transgressions happen within the remit of traditionally conceived intimate or private relationships, and the broadening of what counts as a public figure. The aim of this paper is to interrogate this moral turn in public life by examining how public denunciations are accomplished in broadcast talk, and the role they play in co-constructing and reaffirming perceived common moral ground. We conclude that while moral criticisms, such as accusing, blaming, denouncing, reproaching, and so on, are evidently oriented as sensitive actions in the public sphere, it appears that constraints on publicly denouncing immoral behavior are on the wane.